Perubahan Sifat Fisik dan Mekanik Panel Zephyr Bambu setelah Uji Pelapukan Cuaca The Change of Physical and Mechanical Properties of Zephyr Bamboo Panel after Exposed to Out-door Weathering - Mohamad Gopar; Yanni Sudiyani (Jurnal Ilmu dan Teknologi Kayu Tropis, 2004)
The objective of this study is to evaluate the physical and mechanical properties of zephyr bamboo panel after exposed to outdoor weathering for 12 months. The zephyr bamboo panel is bamboo board which was made from crushed bamboo in bamboo-crushing machine to produce zephyr, the panel was made for exterior type, and the thickness was 18 mm.  The adhesive used was phenol formaldehyde (PF) and urea formaldehyde (UF) with resin content of 17% to dry weight bamboo. Isocyanate was applied to face layer of some panels. The result shows that the properties of zephyr bamboo panel produced by PF resin and layered with Isocyanate was better than panel of UF only.  After 12 months exposure, the properties include the weight, density, thickness swelling and modulus of rupture (MOR) were reduced.  Zephyr panel produced by UF shows the highest reduced properties, while zephyr panel produced by PF still maintained the properties which were met the JIS A 5908 for particleboards